Consensus Good Practice Guidelines for the Use of Long-Term Segregation (LTS) with Autistic People: A Delphi Study - Gilbey, Ben; Baliousis, M.; Tickle, A.; Varela, J.; Woodrow, C. (2024)
Long-Term Segregation (LTS) is used disproportionately with autistic people in Assessment and Treatment Units (ATUs). Recent investigations into the use of LTS with autistic people have highlighted how often LTS was used primarily due to the main ward environment being unsuitable and distressing for the autistic person, rather than due to the need to manage the risk presented by the patient. There have also been instances of LTS being used in an individualised way with autistic people as a means of providing a more appropriate environment in which to provide care whilst they remain in the ATU. This clinical reality presents a difficulty for Multidisciplinary Team (MDT) staff, as current guidance (i.e. The Mental Health Act Code of Practice 1983) stipulates that the use of LTS must end as soon as possible, with the person being integrated back onto the main ward. However, doing so may reinstate the distress that triggered the use of LTS initially. As such there is an urgent need to develop good practice guidelines that can support the MDT to implement LTS with autistic people in a truly person-centred way which is able to meet the needs of this population whilst minimising the risks of poor care highlighted by recent reports. The current study aimed to produce a set of practice guidelines to inform the good practice of LTS with autistic people.